2017
DOI: 10.1039/c7nj00052a
|View full text |Cite
|
Sign up to set email alerts
|

A new and versatile one-pot strategy to synthesize alpha-bromoketones from secondary alcohols using ammonium bromide and oxone

Abstract: A new, efficient and green protocol for the one-pot synthesis of alpha-bromoketones from secondary alcohols is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…α-Bromoketones are important intermediates in the synthesis of various complex molecules. [64][65][66] These 1,2-synthons can be typically accessed from alkenes, [66] alcohols, [67] TMSenolates [68] or ketones, [69] etc. We showed that olefins can Scheme 17 Proposed mechanism for Oxidative Cleavage of an Olefin by in situ-Generated Catalyst 5. be converted to α-bromoketones by treatment with NBS in the presence of IBX in DMSO.…”
Section: One-pot Transformation Of Olefins To α-Bromo-and α-Azidoketonesmentioning
confidence: 99%
“…α-Bromoketones are important intermediates in the synthesis of various complex molecules. [64][65][66] These 1,2-synthons can be typically accessed from alkenes, [66] alcohols, [67] TMSenolates [68] or ketones, [69] etc. We showed that olefins can Scheme 17 Proposed mechanism for Oxidative Cleavage of an Olefin by in situ-Generated Catalyst 5. be converted to α-bromoketones by treatment with NBS in the presence of IBX in DMSO.…”
Section: One-pot Transformation Of Olefins To α-Bromo-and α-Azidoketonesmentioning
confidence: 99%
“…and Oxone ® (3 equiv.) [ 166 ]. This altered procedure yielded 10 α-bromoketones in low to excellent yields (38–94%).…”
Section: Oxidative Halogenation Of Secondary Alcoholsmentioning
confidence: 99%
“…On the other hand, an efficient and green protocol for the synthesis of α-bromoketones 179 a-i from secondary alcohols 178 using non-toxic reagent such as NH 4 Br/oxone in the presence of MeOH/H 2 O solvent mixture was developed by Rammurthy et al in 2017 as shown in the Scheme 56. [151] This reaction occurs in two consecutive steps first oxidation of secondary alcohol to ketones followed by the oxidative bromination of thus formed ketone derivatives to afford the required α-bromoketone products. A proposed mechanism for the formation of α-bromoketones from the starting alcohols is clearly presented in the Scheme 57.…”
Section: Chemistryselectmentioning
confidence: 99%